Prospective motion detection and re‐acquisition in diffusion MRI using a phase image–based method—Application to brain and tongue imaging. Issue 2 (4th March 2021) - Liang, Xiao; Su, Pan; Patil, Sunil G.; Elsaid, Nahla M. H.; Roys, Steven; Stone, Maureen; Gullapalli, Rao P.; Prince, Jerry L.; Zhuo, Jiachen
Abstract : Purpose: To develop an image‐based motion‐robust diffusion MRI (dMRI) acquisition framework that is able to minimize motion artifacts caused by rigid and nonrigid motion, applicable to both brain and tongue dMRI. Methods: We developed a novel prospective motion‐correction technique in dMRI using a phase image–based real‐time motion‐detection method (PITA‐MDD) with re‐acquisition of motion‐corrupted images. The prospective PITA‐MDD acquisition technique was tested in the brains and tongues of volunteers. The subjects were instructed to move their heads or swallow, to induce motion. Motion‐detection efficacy was validated against visual inspection as the gold standard. The effect of the PITA‐MDD technique on diffusion‐parameter estimates was evaluated by comparing reconstructed fiber tracts using tractography with and without re‐acquisition. Results: The prospective PITA‐MDD technique was able to effectively and accurately detect motion‐corrupted data as compared with visual inspection. Tractography results demonstrated that PITA‐MDD motion detection followed by re‐acquisition helps in recovering lost and misshaped fiber tracts in the brain and tongue that would otherwise be corrupted by motion and yield erroneous estimates of the diffusion tensor. Conclusion: A prospective PITA‐MDD technique was developed for dMRI acquisition, providing improved dMRI image quality and motion‐robust diffusion estimation of the brain and tongue.